NG

so sánh 20112012  - 20112011 và 20112011 - 20112010

TL
28 tháng 10 2015 lúc 18:19

20112012 - 20112011 = 20112011.(2011 - 1) = 20112011.2010

20112011 - 20112010 = 20112010.(2011 - 1) = 20112010.2010

Vì 20112011 > 20112010 nên 20112011.2010 > 20112010.2010 

Vậy 20112012 - 20112011 > 20112011 - 20112010

Bình luận (0)
H24

bài làm

20112012 - 20112011 

= 20112011.(2011 - 1)

= 20112011.2010

20112011 - 20112010

 = 20112010.(2011 - 1)

= 20112010.2010

Do 20112011 > 20112010 nên 20112011.2010 > 20112010.2010 

Vậy .....................

hok tốt

Bình luận (0)